Safety huddles in paediatric intensive care unit: implementation and staff perception in a resource limited setting - Zeeshan, Arsheen; Yasmin Hashwani; Muhammad Jawwad; Yousafzai, Muhammad Tahir; Naveed Rehman; Qalab Abbas (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the perception, knowledge, empowerment and comfort level of critical care staff in relation to the implementation of safety huddles in paediatric intensive care unit of a tertiary care hospital. Method: The descriptive cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, from September 2020 to February 2021, and comprised physicians, nurses and paramedics who were part of the safety huddle. Staff perception regarding this activity was evaluated using open-ended questions that were scored on a Likert scale. Data was analysed using STATA 15. Results: Of the 50 participants, 27(54%) were females and 23(46%) were males. Overall, 26(52%) subjects were aged 20-30 years age, while 24(48%) were aged 31-50 years. Of the total, 37(74%) subjects strongly agreed that safety huddle had been routinely held in the unit since initiation; 42(84%) felt comfortable sharing their concerns about patient safety; and 37(74%) considered the huddles worthwhile. Majority 42(84%) felt more empowered through huddle participation. Moreover, 45(90%) participants strongly agreed that daily huddle helped them in becoming clearer about their responsibilities. For safety risk assessment, 41(82%) participants acknowledged that safety risks had been assessed and modified in routine huddles. Conclusion: Safety huddle was found to be a powerful tool to create a safe environment in a paediatric intensive care unit where all team members can speak up freely about patient safety. Key Words: Safety huddle, Staff perception, Staff empowerment, Patient safety in PICU.